PENGARUH LEVERAGE, KOMISARIS INDEPENDEN, DAN INTENSITAS MODAL TERHADAP TAX AVOIDANCE PERUSAHAAN KONSTRUKSI TERDAFTAR BEI 2020 – 2022 - Bambang Ahmad Indarto; Dewi Ari Ani; Arda Raditya Tantra (Jurnal Akuntansi dan Pajak, 2024)
This research investigates the influence of leverage, independent commissioners, and capital intensity on tax avoidance practices in construction companies in Indonesia. Based on multiple linear regression analysis of data on construction companies listed on the Indonesia Stock Exchange for the 2020-2022 period, the findings show that leverage has a significant and negative influence on tax avoidance, while independent commissioners do not have a significant influence. Capital intensity, on the other hand, has a significant and positive influence on tax avoidance. These results indicate that companies tend to use financial structure and capital intensity to manage tax burdens and achieve the desired level of tax avoidance. The implication is that management needs to carefully consider investment policies and capital structure to improve the effectiveness of corporate tax practices. This research suggestion involves increasing the role of independent commissioners in overseeing tax practices as well as careful monitoring of the company's financial structure.